Historical dictionary of Saudi Arabia - Peterson, John 1947- (Rowman & Littlefield, 2020)
The Kingdom of Saudi Arabia now has been under the spotlight of Western curiosity for more than 80 years. More than 15% of the world's total oil reserves lie underneath Saudi Arabia and, in the early 1990s, the kingdom became the world's largest crude oil producer. Not surprisingly, a world highly dependent on oil regards the desert kingdom as an area of intense strategic concern, as reflected in the coalition of forces assembled on Saudi soil to oust Iraq from Kuwait in 1991. Also, it played a major role in the invasion of Saddam Husayn's Iraq in 2003 and shares concern with the West over Iran's nuclear intentions throughout the 21st century. This third edition of Historical Dictionary of Saudi Arabia contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent resource for students, researchers, and anyone wanting to know more about Saudi Arabia.
Literaturangaben
Keywords: Geschichte; Saudi Arabia -- History -- Dictionaries; Saudi-Arabien; Wörterbuch